An investigation into culture and propagation of edible mushrooms on different organic substrates - Seecharran, Diana; Ansari, Abdullah Adil; Subramanian, Gomalthinayagam; Nankishore, Alliea; Sambhu, Hemchandranauth; Punnu, Brian (Mushroom Research, 2018)
Mushrooms, as natural decomposers, play an important role in degrading organic matter in the ecosystem. Mushrooms species differ in their ability to degrade substrates and this would determine their capacity to colonize various substrates Ligninolytic enzymes excreted by the mushrooms degrade cellulose, hemicellulose and lignin, making the substrate more digestible. Pleurotus species are one of the most common edible mushrooms. They are primary decomposers and can be grown on a range agricultural waste. This study cultivated Pleurotus ostreatus on rice straw, supplemented with cattle dung, duck manure or vermicompost. The final vermicompost substrate had the least amount of nutrients but produced mushrooms with the highest mineral content and the best growth parameters.Â  The mineral content of mushrooms determines their nutritional value. The mushrooms produced had a high moisture content (85 â€“ 94%), which confirms with the findings of previous studies.